Cardiac Arrest due to Recurrent Ventricular Fibrillation Triggered by Unifocal Ventricular Premature Complexes in a Silent Myocardial Infarction - Dong Hyun Lee; Seul Lee; Hyo Jin Jung; Soo Jin Kim; Jeong Min Seo; Jae Hyuk Choi; Jong Sung Park (Korean Journal of Critical Care Medicine, 2014)
A 51-year-old male patient was referred for a sudden out-of-hospital cardiac arrest. Upon arrival, he was conscious and had no chest pain complaints. There was no abnormality in initial electrocardiographic and echocardiographic examinations. However, episodes of recurrent ventricular fibrillation (VF) were documented on rhythm monitoring. Each VF episode was triggered by an isolated monomorphic ventricular premature complex (VPC). Suspecting idiopathic VF, emergency radiofrequency catheter ablation was planned for the VPCs. However, when coronary angiography was performed to exclude silent ischemia, the results showed a total occlusion of the right coronary artery posterolateral branch, which is thought to supply the left ventricular inferior and septal wall. After successful reperfusion, VF episodes and the triggering VPCs disappeared. We are documenting this case to emphasize the potential for silent myocardial infarction to cause out-of-hospital sudden cardiac arrest even in a patient without any symptom or sign of acute coronary syndrome.